KEKUATAN HUKUM PEMBUKTIAN PERALIHAN HAK GANTI RUGI (PHGR) NOTARIS SEBAGAI SYARAT UNTUK PENDAFTARAN HAKNYA - ITA RISNAWATY PURBA (PREMISE LAW JURNAL, 2016)
In conclusion, Notary’s PHGR Deed also has proving legal force as the ground of the right when the title is to be registered for receiving the land ownership right and also having legal force to prove as evidence in court of justice. This is proven in a decision of the rulling of district court No.76/Pdt//2014/PT-Mdn dated April 16,  which has won PHGR deed as the land owner. This showing that even the right of land certificate is a letter evidence of right that happened as a strong and perfect, but if physical date and or judicial date on it has wrong, so will be a weak evidence. In this case the officer which is issued proof of the right do not pay attention to the principle of accuracy to the ground object, in the issueance of the certificate. The principle of the negative publicity that is practiced in our country open opportunities to do the rebuttal although the land who has registered his rights in the national land agency. So with the notarial deed which is the authentic deed that has been set by law. There is a good Notaries still act professional, by using the principle of awareness with first make sure that the PHGR deed have legal certainty before making it. Notary PHGR deed has the strength of evidence and can be used as the pedestal of the right to be registered to the National Land Agency. Keywords: Notarial PHGR Deed, Right Transfer